MAKNA REDUPLIKASI DALAM NOVEL “RUMAH UNTUK ALIE” KARYA LENN LIU : KAJIAN MORFOLOGI - Restia; Israwati Amir; Aria Bayu Setiaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and describe the meaning of reduplication in Lenn Liu's novel Rumah untuk Alie (Home for Alie) based on a morphological study. The research method used is a qualitative descriptive method with a literature study approach. The data for this study consist of sentences containing reduplication meanings collected through reading, note-taking, and documentation techniques. This novel was chosen as the research object because it presents a reflective, emotional, and poetic style of language, thus utilizing reduplication extensively aesthetically. The results of this study indicate that the novel Rumah untuk Alie found 117 data of reduplication meanings which include 35 plural meanings (many), 8 diverse meanings, 5 similar meanings, 7 phoneme changes, 58 intensity meanings, and 4 reciprocal meanings. Reduplication with intensity meaning is the most dominant meaning, showing emphasis on the feelings, actions, and conditions of the characters expressively. Reduplication with plural meanings is used to clarify the description of the situation, while reduplication with diverse and similar meanings serves to enrich the description and provide an imaginative effect. In addition, reduplication with phoneme changes and reduplication with reciprocal meanings are used to emphasize idiomatic meanings and describe interactions between characters. These findings indicate that the use of reduplication in the novel not only beautifies the language, but also supports the delivery of messages and the expression of characters' emotions effectively.